PENENTUAN NILAI KALOR JENIS LOGAM MENGGUNAKAN METODE KALORIMETER BERDASARKAN ASAS BLACK - Sri Minartih; Syakiraturrahmah; Jeliana Veronika Sirait (Universitas Muhammadiyah Metro, 2026)
Abstract: This study aims to determine the specific heat values of three types of metals, namely aluminum, brass, and copper, using the calorimeter method based on Black's Principle. The experiment was carried out by heating the metals to a certain temperature and then transferring them into a calorimeter containing water. The equilibrium temperature was recorded to calculate the heat absorbed by the water and the heat released by the metals. The results showed that the average specific heat values obtained were 0.42 cal/g℃ for aluminum, 0.16 cal/g℃ for brass, and 0.13 cal/g℃ for copper. These results are consistent with the theoretical values, although there are deviations caused by heat loss to the environment and limitations of the measuring instrument. Critical analysis identified that the use of an analog thermometer and suboptimal calorimeter insulation were the main factors of inaccuracy. As a recommendation, the use of a digital temperature sensor and the addition of thermal insulation can improve measurement accuracy. This study concluded that the calorimeter method can be used to determine the specific heat of metals with a sufficient level of confidence, provided that interfering factors can be minimized.